2018
DOI: 10.1002/stem.2885
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Disease Mutations of Splicing Factor SRSF2 Cause G2-M Arrest and Skewed Differentiation of Human Hematopoietic Stem and Progenitor Cells

Abstract: Myeloid malignancies, including myelodysplastic syndromes, chronic myelomonocytic leukemia, and acute myeloid leukemia, are characterized by abnormal proliferation and differentiation of hematopoietic stem and progenitor cells (HSPCs). Reports on analysis of bone marrow samples from patients have revealed a high incidence of mutations in splicing factors in early stem and progenitor cell clones, but the mechanisms underlying transformation of HSPCs harboring these mutations remain unknown. Using ex vivo cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
(108 reference statements)
2
23
1
1
Order By: Relevance
“…Furthermore, the splicing factors SRSF2 and U2AF1 seem to impact skewing. Mutations in both SRSF2 and U2AF1 cause abnormal differentiation by skewing granulo-monocytic differentiation towards monocytes [4]. On the other hand, nonmalignant conditions may also contribute to in vitro myelomonocytic skewing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the splicing factors SRSF2 and U2AF1 seem to impact skewing. Mutations in both SRSF2 and U2AF1 cause abnormal differentiation by skewing granulo-monocytic differentiation towards monocytes [4]. On the other hand, nonmalignant conditions may also contribute to in vitro myelomonocytic skewing.…”
Section: Discussionmentioning
confidence: 99%
“…21 During human HSPCs megakaryo-erythroid differentiation, expression of U2AF1-S34F and U2AF1-Q157R resulted in a decrease in the megakaryocyte with a compensatory increase in the erythroid precursors populations. 27 However, it has remained unclear whether depletion of U2AF1 plays any vital role in human erythropoiesis. We analysed the expression of three isoforms of U2AF1 on the sorted cells during human erythropoiesis.…”
Section: Mutations Of U2af1 Have Been Implicated In Mds Patientsmentioning
confidence: 99%
“…24,25 Recently study revealed some spliceosome components, such as SF3B1 and SRSF2 deficiency impairs human erythropoiesis. 26,27 But the functions of depletion U2AF1 in erythropoiesis remain unknown.…”
mentioning
confidence: 99%
“…An advantage of this protocol is that it allows differentiation along all four myeloid populations, namely monocytes, granulocytes, megakaryocytes, and erythrocytes. Thus, it can be employed for studying normal myeloid differentiation and for investigating the impact of myeloid disease (myelodysplastic syndromes, acute myeloid leukemia, myeloproliferative neoplasms, and others) associated point mutations and chromosomal translocations on molecular and cellular phenotype during proliferation and differentiation of CD34 + cells 11,12,[23][24][25] . This protocol can also be employed for examining the impact of anti-and pro-inflammatory cytokines, and of potential therapeutic drugs on myeloid differentiation [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo differentiation of umbilical cord blood derived CD34 + HSPCs is a widely applied model for investigating normal hematopoiesis and hematopoietic disease mechanisms. When cultured with the appropriate cytokines, the UCB CD34 + HSPCs can be induced to differentiate along the myeloid or lymphoid lineages [11][12][13][14][15][16] . Here, we describe protocols for isolation and immunophenotypic characterization of the CD34 + HSPCs from human UCB, and for their differentiation to myeloid lineage cells.…”
Section: Introductionmentioning
confidence: 99%